PERBANDINGAN KADAR LDL DAN HDL PADA PENDERITA STROKE ISKEMIK DENGAN STROKE HEMORAGIK DI RUMAH SAKIT UMUM HAJI KOTA MEDAN - DESI ELISA FLOWER; ISRA THRISTY (LP2MTBM MAKARIOZ, 2021)
Stroke occurs in a blood vessel in the brain which is caused by a blockage and rupture of blood vessels in the brain.Broadly speaking, strokes are divided into two, including ischemic stroke and hemorrhagic stroke. Stoke is also closelyrelated to LDL and HDL levels, because LDL and HDL levels influence atherosclerosis which is part of the pathophysiologicalprocess of stroke. Comparing LDL and HDL levels in ischemic and hemorrhagic strokes in Medan Hajj General Hospital. Thestudy used secondary data, namely LDL and HDL levels in patients with ischemic and hemorrhagic strokes by collectingmedical records according to the determined sample size. The average of ischemic stroke patients was 43.85 mg / dl,hemorrhagic stroke patients had HDL levels of 41.07 mg / dl. LDL levels in ischemic stroke patients are 139.07 mg / dl andhemorrhagic stroke patients are 81.21 mg / dl. Based on the results of the study There is no comparison between HDL levelsin ischemic stroke patients and hemorrhagic patients, there is a comparison between LDL levels in ischemic stroke patientsand hemorrhagic patients.